Complications of percutaneous nephrostomy in a district general hospital - Turo, Rafal (Turk J Urol, 2018)
OBJECTIVE: Percutaneous nephrostomy (PCN) is one of the commonest procedures performed. There are currently no European recommendations on the accepted rate of complications. The aim of the present study is to report the complication rate of PCN with the specific emphasis on sepsis and septic shock, the causative organisms, sensitivities to antibiotics, and associated risk factors. MATERIAL AND METHODS: Retrospectively collected data on patients undergoing acute or elective PCN at the Department of Radiology, Countess of Chester Hospital (COCH), in the UK between January 2014 and December 2016 were analyzed after the study was approved by Local Audit Department at COCH. RESULTS: A total of 66 patients underwent 90 acute or elective PCNs. Three patients developed major post-PCN complication (two patients developed septic shock and the third suffered a hemorrhagic episode requiring blood transfusion). Nephrostomy tube complications (blockage, leaking, fracturing and kinking of the catheter) occurred in 4 patients. Complications were more common when the PCN was performed out of working hours (71.4% [10/14], and 17.3% [9/52] for PCNs performed within, and out of working hours, respectively: p<0.001). The age of the patients did not seem to correlate with the development of complications (p<0.001). Of all 25 patients, in whom septicemia was diagnosed prior to PCN tube insertion, 12 developed septic shock and 13 had signs of sepsis for longer than 24 h. Fifteen patients had positive urine cultures. The most common organism isolated was Escherichia coli. Blood culture isolates included: Escherichia coli, Eggerthella lenta, Enterococcus, Proteus mirabilis, Pseudomonas aeruginosa and Streptococcus pneumonia. CONCLUSION: Our complication rates were within United States proposed target ranges. Our data may help to serve as a baseline for outcome targets in the European centres.